2016
DOI: 10.1016/j.revpalbo.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Albian angiosperm pollen from shallow marine strata in the Lusitanian Basin, Portugal

Abstract: The evolution of angiosperms significantly changed the composition of the terrestrial vegetation during the mid-Cretaceous. In contrast to the wealth of information available on the biology and systematic relationships of early angiosperms, the temporal patterns of their evolution and radiation are poorly constrained. Here we present a continuous angiosperm pollen record from well-dated shallow marine deposits in the Lusitanian Basin, Portugal. The São Julião section provides a solid stratigraphic framework to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 59 publications
1
26
0
2
Order By: Relevance
“…The absence of such types supports the hypothesis that the Glen Rose horizons studied are older than the base of Zone II. Horikx et al (2016) reported pollen close to two of these, T. sagax and S. vermimurus, from the late early Albian of Portugal, suggesting that they may not all appear at the same time.…”
Section: Correlation Of the Glen Rose Samples With The Potomac Group mentioning
confidence: 98%
See 4 more Smart Citations
“…The absence of such types supports the hypothesis that the Glen Rose horizons studied are older than the base of Zone II. Horikx et al (2016) reported pollen close to two of these, T. sagax and S. vermimurus, from the late early Albian of Portugal, suggesting that they may not all appear at the same time.…”
Section: Correlation Of the Glen Rose Samples With The Potomac Group mentioning
confidence: 98%
“…Similar to Retimonocolpites sp. 7 of Heimhofer et al (2007), which was assigned to R. dividuus by Horikx et al (2016).…”
Section: Monosulcatesmentioning
confidence: 99%
See 3 more Smart Citations